THE ROLE OF CAROTENOIDS IN PREVENTING OXIDATIVE STRESS: EXPLORING THE ANTIOXIDANT POTENTIAL OF PUMPKIN AS A FUNCTIONAL CROP - Matić, Milana; Stupar, Alena; Kebert, Marko; Kiprovski, Biljana; Brdar-Jokanović, Milka (Food and Feed Research, 2025)
This review paper aims to explore the antioxidant properties of carotenoids and their role in mitigating oxidative stress caused by reactive oxygen species (ROS). Excessive ROS levels are linked to cellular damage, contributing to chronic diseases such as cancer, cardiovascular disorders, and neurodegenerative conditions. Carotenoids, natural pigments in various fruits and vegetables, exhibit significant antioxidant activity by neutralizing ROS and protecting cellular components. This paper highlights how carotenoids combat oxidative stress, emphasizing their ability to scavenge free radicals and prevent further lipid, protein, and DNA damage. Pumpkin (Cucurbita spp.) stands out as a valuable alternative crop due to its high carotenoid content, potential for sustainable cultivation, and versatility in developing functional foods and nutraceuticals. Among carotenoid-rich sources, pumpkins are distinguished by their high β-carotene content and additional carotenoids like lutein and zeaxanthin. These compounds not only enhance antioxidant defenses but also provide provitamin A activity, contributing to overall health. The review further discusses factors influencing carotenoid content in pumpkins, including cultivation practices, and post-harvest storage conditions. It also examines the impact of processing methods on carotenoid bioavailability, highlighting techniques such as steaming and freeze-drying that optimize nutrient retention. Key findings underscore the relevance of pumpkins as a sustainable and cost-effective source of carotenoids, suitable for functional food development. Promoting the inclusion of pumpkin-based products in diets is proposed as a practical strategy to combat oxidative stress and support public health.